0794 Reduction in Restless Legs Syndrome Symptoms with Non-Invasive Peripheral Nerve Stimulation. (27th May 2020) - Charlesworth, J D; Baker, F C; Kolotovska, V; Adlou, B; de Zambotti, M; Ismail, M; Raghunathan, S; Singh, H; Buchfuhrer, M J
Abstract: Introduction: Restless Legs Syndrome (RLS) is a sensorimotor neurological condition characterized by an uncontrollable urge to move the legs that interferes with falling and staying asleep. For the over 5 million Americans with clinically significant RLS, these symptoms occur multiple nights per week, significantly impair quality of life, increase the prevalence of depression and anxiety, and increase suicide risk. FDA-approved medications for RLS are associated with progressively worsening RLS symptoms and numerous adverse events, whereas existing medical device treatments have limited efficacy. Methods: We evaluated a novel neurostimulation intervention for RLS developed by Noctrix Health; electrical stimulation was applied non-invasively and bilaterally to the peroneal nerve of patients with moderate-to-severe primary RLS. Stimulation parameters were engineered to maximize therapeutic efficacy while minimizing interference with sleep. To assess the therapeutic efficacy of this technique, we conducted a multi-site randomized patient-blinded crossover trial comparing active neurostimulation treatment to a sham device. Following a lab visit for calibration, optimization, and training, each patient was instructed to self-administer each treatment - active and sham - for 14 consecutive nights at home. Results: Active neurostimulation treatment resulted in a clinically significant reduction in RLS severity of 4.2 points on the International RLS Rating Scale (IRLS) relative to sham (P<0.01), comparable to FDA-approved medications. Moreover, 79% of patients demonstrated a clinically significant improvement on the Clinical Global Impressions-Improvement scale (CGI-I) compared to 7% for sham (P<0.01). Conclusion: To our knowledge, this is the first sham-controlled study demonstrating a clinically significant reduction in RLS severity resulting from a non-pharmacological intervention. This therapeutic effect was sustained over 2-weeks of in-home patient-administered usage, indicating consistent efficacy. A medical device based on this technology could be a promising alternative or complement to medications. Support: Funding was provided by Noctrix Health, Inc.